Single cell biology—a Keystone Symposia report. Issue 1 (3rd October 2021) - Cable, Jennifer; Elowitz, Michael B.; Domingos, Ana I.; Habib, Naomi; Itzkovitz, Shalev; Hamidzada, Homaira; Balzer, Michael S.; Yanai, Itai; Liberali, Prisca; Whited, Jessica; Streets, Aaron; Cai, Long; et al.
Abstract: Single cell biology has the potential to elucidate many critical biological processes and diseases, from development and regeneration to cancer. Single cell analyses are uncovering the molecular diversity of cells, revealing a clearer picture of the variation among and between different cell types. New techniques are beginning to unravel how differences in cell state—transcriptional, epigenetic, and other characteristics—can lead to different cell fates among genetically identical cells, which underlies complex processes such as embryonic development, drug resistance, response to injury, and cellular reprogramming. Single cell technologies also pose significant challenges relating to processing and analyzing vast amounts of data collected. To realize the potential of single cell technologies, new computational approaches are needed. On March 17–19, 2021, experts in single cell biology met virtually for the Keystone eSymposium "Single Cell Biology" to discuss advances both in single cell applications and technologies. Abstract : Single cell biology seeks to elucidate critical biological processes and diseases, from development and regeneration to cancer. New techniques are beginning to unravel how differences in cell state lead to different cell fates among genetically identical cells, which underlies complex processes such as embryonic development, response to injury, cellular reprogramming, and drug resistance. On Demand content : https://keysym.us/21EK26NYAS